Potensi Quercetin Sebagai Agen Antidiabetes Pada Model Tikus Diabetes Mellitus Tipe 2: Tinjauan Literatur Sistematis - Rizkya Ariyanti Ananda Derya Ananda (LPPM STIKES Marendeng Majene, 2026)
Diabetes mellitus (DM) is metabolic disorder characterized by elevated blood sugar levels due to insulin dysfunction. Research on natural compounds as alternative therapies is growing, one of which is quercetin which is known to have antidiabetic effects. This study aims to analyze the scientific literature related to the potential of quercetin as an antidiabetic in a rat model of type 2 diabetes mellitus. The method used in this study was a systematic literature review using the PRISMA approach, with data obtained from two main databases, Google Scholar and Pubmed, from 2015 to 2026. A search using the keywords “quercetin”, “type 2 diabetes”, and “rats”. From the total articles identified, five studies met the final inclusion criteria and were analyzed. The results showed that quercetin has a role in lowering blood sugar levels, improving insulin levels, and has a protective effect on pancreatic ?-cell damage. However, the available evidence remains limited to animal studies, and further clinical research is required before the findings can be generalized to humans or applied as a therapeutic option for diabetes management.